2019
DOI: 10.1182/blood-2019-129409
|View full text |Cite
|
Sign up to set email alerts
|

Th1 Cytokine Polymorphism Gene: TNF-Alpha -857C/T Affects the Pathogenesis and Progression of Acute Myeloid Leukemia

Abstract: Background: Acute myeloid leukemia (AML) is a hematological malignancy characterized by the autonomous growth of immature myeloid cells with impaired differentiation and maturation. Cytokines are low-molecular-weight proteins that play a basic and fundamental role in communication within the immune system. Cytokines induce various effects such as differentiation, proliferation, hematopoiesis, and inflammation of target cells. AML is also closely associated with cytokine networks in terms of proliferation, apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The polymorphism of the TNF-α (−857) C/T TT genotype ‘higher expressers’ was associated with the risk of AML leukemogenesis [ 63 ]. Other studies focusing on the TNF-α rs1800629 SNP (−308G/A) have revealed that the G/G ‘low expresser’ genotype was associated with a high risk of adult B-ALL in Sudanese patients, while the −308G/A polymorphism was linked to SLE [ 64 , 65 ] and AML mortality [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphism of the TNF-α (−857) C/T TT genotype ‘higher expressers’ was associated with the risk of AML leukemogenesis [ 63 ]. Other studies focusing on the TNF-α rs1800629 SNP (−308G/A) have revealed that the G/G ‘low expresser’ genotype was associated with a high risk of adult B-ALL in Sudanese patients, while the −308G/A polymorphism was linked to SLE [ 64 , 65 ] and AML mortality [ 66 ].…”
Section: Discussionmentioning
confidence: 99%